Fiziceskaja kul'tura i sport kak sfera pravovogo regulirovanija - Sevcenko, O. A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The article is devoted to the research of the role of sports in the life of person, society, state. The state policy in the field of physical culture and sports is considered. The rights of citizens on the occupation of physical culture and sports are analyzed. In the article the basic concepts of the field of physical culture and sports are formulated, the classification of kinds of sports is listed. The analysis of the specified materials is necessary for understanding the essence of physical culture and sports, the mechanisms of functioning and predestination in the life of society.